The Baseball Whisperer : a small-town coach who shaped Big League dreams - Tackett, Michael (Houghton Mifflin Harcourt, 2016)
"Traces the ... story of Merl Eberly and his Clarinda A's baseball team, which he tended over the course of five decades, transforming them from a town team to a collegiate summer league powerhouse. Along with Ozzie Smith, future manager Bud Black, and star player Von Hayes, Merl developed scores of major league players (six of which are currently playing). In the process, Merl taught them to be men, insisting on hard work, integrity, and responsibility"--Dust jacket flap.